ApProgXimate audio: a distributed interactive experiment in sound art and live coding. Issue 2 (2nd July 2016) - Kiefer, Chris
ABSTRACT: ApProgXimate Audio is a browser-based sound art experiment, a distributed and participatory piece where code and livecoding are fundamental to the participants' experience. The piece is based on a coding technique called Approximate Programming. It allows participants to explore complex sound synthesis algorithms through relatively simple techniques, by writing and editing code and through screen-based mouse interaction. It foregrounds code as the primary medium of engagement. This article explains the technical background behind the piece, and then explores the design philosophy through three themes that emerged during its creation: accessibility and paths to engagement in work based on live coding, the blurred boundaries between tools, instruments and artworks, and finally issues surround the web-browser as a venue for creative work.